2015
DOI: 10.1093/jnci/djv199
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Inflammation Markers, Risk of Lung Cancer, and Utility for Risk Stratification

Abstract: Circulating levels of CRP, SAA, sTNFRII, and CXCL9/MIG were reproducibly associated with lung cancer risk in two independent studies within the Prostate, Lung, Colorectal, and Ovarian Cancer Screening Trial, underscoring an etiologic role for inflammation in lung carcinogenesis, though replication is needed in other populations. Markers did not improve lung cancer risk stratification beyond standard demographic and behavioral characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
89
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(100 citation statements)
references
References 33 publications
7
89
4
Order By: Relevance
“…The results showed that CXCL9 was associated with lung cancer risk in the replication study, and remained associated with it more than 6 years prior to diagnosis in pooled analyses. Their research suggested that CXCL9 has an etiologic role in lung cancer . On the contrary, Nakanishi et al.…”
Section: Cxcl9 As a Tumor Promotermentioning
confidence: 96%
“…The results showed that CXCL9 was associated with lung cancer risk in the replication study, and remained associated with it more than 6 years prior to diagnosis in pooled analyses. Their research suggested that CXCL9 has an etiologic role in lung cancer . On the contrary, Nakanishi et al.…”
Section: Cxcl9 As a Tumor Promotermentioning
confidence: 96%
“…The hope is that these inflammatory biomarkers will allow oncologists to determine the risk of tumorigenesis or tumor recurrence after surgery. Supporting this approach, inflammation-related biomarkers in plasma have been found to be associated with a higher risk of developing lung cancer: C-reactive protein, serum amyloid A, soluble tumor necrosis factor receptor-2 and monokine induced by gamma interferon (CXCL9/MIG) were more prevalent in the blood of patients who went on to develop cancer (95). Other biomarker approaches are simpler and easily implemented.…”
Section: The Role Of Inflammation In Cancer Initiationmentioning
confidence: 99%
“…28 Given its ability to measure chronic inflammation, CRP has been studied in the lung cancer context as both a measurement of lung cancer risk and as a prognostic marker of disease activity once lung cancer has been diagnosed. 29,30 However, it has not been studied in relation to depression in lung cancer or while undergoing anticancer treatments. Understanding its role as a marker of inflammation that may be associated with the presence of depression in patients with metastatic lung cancer has important and specific treatment implications.…”
Section: Introductionmentioning
confidence: 99%